Culture of patient safety and overload of work: perceptions of nursing workers (Research, Society and Development, 2020)
The aim of this work is to know the perceptions of nursing workers about the safety culture of the patient and their relation with the work demand. This is a descriptive and exploratory study with a qualitative approach carried out in a hospital admission unit, which has 27 hospital beds. Results: Participants perceive the patient's safety culture as individual actions to provide care to minimize the occurrence of errors, not mentioning the perception of the collective exchange of thoughts and attitudes. Still, they report that the high demand of work puts the patient at the mercy of the possible errors that can undertake them. The interviewed workers, for the most part, have a perception of the safety culture of the patient as being equivalent to patient safety. They also point out that work overload has a negative influence on the safety culture.